Thermodynamic evaluation of Denizli Kizildere geothermal power plant and its performance improvement - Dagdas, A; Öztürk, R; Bekdemir, S (PERGAMON-ELSEVIER SCIENCE LTD, 2005)
A thermodynamic optimization of the Denizli Kizildere power plant is performed using real data, and some important results are obtained. The optimum flashing pressure is found to be 200 kPa. According to the existing geothermal power plant, 18% power augmentation is provided when the plant operates at this state. In addition, a new flash-binary model is proposed, and the optimum operating pressure is found that makes the power output maximum. In this model, the maximum power is found to be 18,238 kW,. This means that 93.2% more power is obtained than that of the existing plant. Apart from that, the most suitable working fluid is investigated for the binary cycle. (C) 2004 Elsevier Ltd. All rights reserved.
Keywords: geothermal power plant; power generation; exergy analysis; Denizli; TURKEY; Thermodynamics; Energy & Fuels; Mechanics